Anti-ultraviolet aging polylactic acid composite fiber membrane and preparation method thereof
Through the graft modification and electrospinning technology of nanotitanium dioxide and benzophenone derivatives, the problems of the polylactic fiber membrane's resistance to UV aging and low mechanical properties are solved, and stronger ultraviolet shielding and mechanical properties are achieved. , ensuring the stability and wide application of fiber membranes.
Patent Information
- Application Number
- CN202411784093.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure CN119265746A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fiber membranes, in particular to an anti-ultraviolet aging polylactic acid composite fiber membrane and a preparation method thereof. Background Art
[0002] Traditional film substrates are made of petroleum-based plastics, which have advantages such as good processability, low cost and excellent physical properties. However, these plastics are non-degradable. Discarded petroleum-based plastics not only cause soil and water pollution, but also produce greenhouse gases, microplastics and other harmful byproducts. In order to solve this problem, biodegradable and renewable bio-based polymers have been developed as film substrates to replace petroleum-based packaging materials. Polylactic acid (PLA) is made from corn, wood residues or other biomaterials and has become one of the most promising polymers due to its non-toxicity, good biocompatibility and excellent mechanical properties. However, the anti-UV aging effect of PLA film is poor, which limits its application in a wide range of fields.
[0003] In order to solve the problem of poor anti-ultraviolet aging ability of polylactic acid-based films, researchers have made a lot of efforts, such as the Chinese patent publication number CN109401250B, which discloses a polylactic acid composite material with anti-ultraviolet aging and a preparation method thereof, and the Chinese patent publication number CN109338503A, which discloses a preparation method of polylactic acid fiber with anti-ultraviolet aging. Although both increase the anti-ultraviolet aging ability of polylactic acid, they still have the problem of high addition amount and unsatisfactory anti-ultraviolet aging effect. Nano inorganic materials have strong absorption and shielding effects on ultraviolet rays. Among them, nano-TiO2 can reflect and scatter long ultraviolet rays and absorb ultraviolet rays in the medium wavelength region, so it can be used as a promising anti-UV aging agent. Benzophenone and its derivatives are one of the most commonly used ultraviolet absorbers. They can absorb or reflect ultraviolet radiation in the UVA and UVB ranges, thereby promoting the widespread use of these products in a variety of applications. However, benzophenone and its derivatives are small molecular structures and are easily precipitated during use, resulting in unstable anti-UV aging effects of the matrix material. Therefore, grafting them on the surface of inorganic matter can effectively improve such problems.
[0004] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides an anti-ultraviolet aging polylactic acid composite fiber membrane and a preparation method, which solves the problems of poor anti-ultraviolet aging ability and low mechanical properties of the polylactic acid fiber membrane.
[0005] (II) Technical solution To achieve the above object, the present invention provides the following technical solution: a polylactic acid composite fiber membrane resistant to ultraviolet aging, wherein the preparation method of the polylactic acid composite fiber membrane resistant to ultraviolet aging comprises the following steps: (1) Ultrasonic dispersion of nano-titanium dioxide in toluene solvent, then adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane, stirring evenly, heating to 70-100°C for reaction for 2-6 hours, filtering after the reaction, washing with ethanol to obtain epoxidized nano-titanium dioxide; (2) dissolving the single-terminated amino polyethylene glycol in a deionized water solution, adjusting the pH to 9-10 with ammonia water, and then adding epoxidized nano-titanium dioxide to react. After the reaction is completed, filtering, and washing with deionized water to obtain polyethylene glycol-grafted nano-titanium dioxide; (3) placing polyethylene glycol grafted nano-titanium dioxide and toluene in a reaction bottle, removing moisture, then adding metallic sodium under a nitrogen atmosphere, heating to the reaction temperature for reaction, filtering after the reaction is completed, and washing with ethanol to obtain polyethylene glycol sodium grafted nano-titanium dioxide; (4) Grafting sodium polyethylene glycol onto nano-titanium dioxide and 16 H 14 The 2-hydroxy-4-glycidyl ether-benzophenone of O4 is dispersed in a xylene solvent, stirred evenly, and reacted. After the reaction is completed, the mixture is filtered and washed with ethanol to obtain benzophenone-based polyethylene glycol-grafted nano-titanium dioxide; (5) Dissolve polylactic acid in a mixed solvent of dichloromethane and N,N-dimethylformamide. After complete dissolution, add benzophenone-based polyethylene glycol grafted nano-titanium dioxide and stir evenly. Transfer it to a syringe, adjust the spinning distance to 15-25 cm, the spinning voltage to 15-20 kV, and the spinning speed to 0.8-2 mL / h, and then perform electrospinning to obtain an anti-UV aging polylactic acid composite fiber membrane.
[0006] Preferably, in step (1), the mass ratio of nano-titanium dioxide, toluene and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 100:1500-3000:40-80.
[0007] Preferably, in step (2), the mass ratio of single-terminated amino polyethylene glycol, deionized water and epoxidized nano-titanium dioxide is 180-300:2400-4000:100.
[0008] Preferably, in step (2), the reaction temperature is 60-90° C. and the reaction time is 3-8 h.
[0009] Preferably, in step (3), the mass ratio of polyethylene glycol grafted nano-titanium dioxide, toluene and metallic sodium is 100:1600-3000:0.3-1.
[0010] Preferably, in step (3), the reaction temperature is 90-120° C. and the reaction time is 12-36 h.
[0011] Preferably, in step (4), the mass ratio of sodium polyethylene glycol grafted nano-titanium dioxide, 2-hydroxy-4-glycidyl ether-benzophenone and xylene is 100:35-80:1500-3000.
[0012] Preferably, in step (4), the reaction temperature is 60-100° C. and the reaction time is 6-15 h.
[0013] Preferably, in step (5), the mass ratio of polylactic acid, dichloromethane, N,N-dimethylformamide and benzophenone-based polyethylene glycol grafted nano-titanium dioxide is 100:140-280:60-120:1.5-5.
[0014] 3. Beneficial technical effects Compared with the prior art, the present invention has the following experimental principles and beneficial technical effects: The invention discloses an anti-ultraviolet aging polylactic acid composite fiber membrane. Firstly, γ-(2,3-epoxypropoxy)propyltrimethoxysilane is used to modify nano titanium dioxide to obtain epoxidized nano titanium dioxide. Then, under alkaline conditions, the epoxy groups of the epoxidized nano titanium dioxide and the amino groups of single-terminal amino polyethylene glycol are subjected to a ring-opening reaction to obtain polyethylene glycol-grafted nano titanium dioxide. Then, under nitrogen anhydrous conditions, the polyethylene glycol-grafted nano titanium dioxide is modified with metallic sodium to obtain polyethylene glycol-sodium-grafted nano titanium dioxide. Then, the polyethylene glycol-sodium-grafted nano titanium dioxide and the epoxy groups of 2-hydroxy-4-glycidyl ether-benzophenone are subjected to a ring-opening reaction to obtain benzophenone-based polyethylene glycol-grafted nano titanium dioxide. Finally, an electrostatic spinning technology is used to obtain the anti-ultraviolet aging polylactic acid composite fiber membrane.
[0015] The anti-ultraviolet aging polylactic acid composite fiber membrane has stronger mechanical properties and anti-ultraviolet aging ability than pure phase polylactic acid fiber membrane. Nano-titanium dioxide is a broadband semiconductor additive material, which can form a network structure with the organic matrix to disperse the external stress inside the fiber membrane when the fiber membrane is subjected to external force, thereby avoiding damage caused by stress concentration and improving the mechanical properties of the fiber membrane. Moreover, when added to the polylactic acid fiber membrane, the hole conduction band structure without electrons and the valence band structure full of electrons of the nano-titanium dioxide are used to prohibit photons with large band gap energy from being absorbed by it when it is exposed to light, thereby causing electron transition behavior, and electrons are transferred from the valence band to the conduction band structure, leaving holes to form an electron-hole structure, thereby increasing the ultraviolet absorption ability of the polylactic acid fiber membrane and converting light energy into heat energy. In addition, the nano-titanium dioxide has ultraviolet shielding ability and is effective in resisting ultraviolet radiation. The benzophenone derivatives can be added to the polylactic acid fiber membrane as a UV absorber. The ketone group in the structure forms an internal hydrogen chelate ring with the ortho-hydroxyl group. When exposed to ultraviolet light, the ultraviolet energy is converted into heat energy through the reversible conversion between the phenolic type and the quinone type, thereby achieving the anti-ultraviolet aging effect of the polylactic acid fiber membrane. The benzophenone derivatives are grafted on the surface of the nano-titanium dioxide, which can not only increase the anti-ultraviolet aging ability of the polylactic acid fiber membrane, but also avoid the instability of the anti-ultraviolet aging effect caused by the precipitation of small molecules, thereby improving its stability. Polyethylene glycol has good compatibility with polylactic acid. The polyethylene glycol chain is grafted on the surface of the nano-titanium dioxide, which can increase the compatibility between the nano-titanium dioxide and polylactic acid, making its dispersion more uniform, thereby improving the anti-ultraviolet aging and mechanical properties of the nano-titanium dioxide in the polylactic acid fiber membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is the reaction formula of single-terminated amino polyethylene glycol and epoxidized nano-titanium dioxide; Figure 2 It is the reaction formula of sodium polyethylene glycol grafted with nano titanium dioxide and 2-hydroxy-4-glycidyl ether-benzophenone. DETAILED DESCRIPTION
[0017] To achieve the above object, the present invention provides the following specific implementation methods and examples: A preparation method of a polylactic acid composite fiber membrane resistant to ultraviolet aging comprises the following steps: (1) According to the mass ratio of 100:1500-3000:40-80, nano-titanium dioxide is ultrasonically dispersed in toluene solvent, and then γ-(2,3-epoxypropoxy)propyltrimethoxysilane is added thereto, and after stirring evenly, the temperature is raised to 70-100°C for reaction for 2-6 hours. After the reaction is completed, the mixture is filtered and washed with ethanol to obtain epoxidized nano-titanium dioxide; (2) Dissolve the single-terminated amino polyethylene glycol in a deionized water solution at a mass ratio of 180-300:2400-4000:100, adjust the pH to 9-10 with ammonia water, then add epoxidized nano-titanium dioxide, react at 60-90°C for 3-8h, filter after the reaction is completed, and wash with deionized water to obtain polyethylene glycol-grafted nano-titanium dioxide; (3) placing polyethylene glycol grafted nano-titanium dioxide and toluene in a reaction bottle at a mass ratio of 100:1600-3000:0.3-1, removing moisture, then adding metallic sodium under a nitrogen atmosphere, heating to 90-120°C for reaction for 12-36 hours, filtering after the reaction is completed, and washing with ethanol to obtain polyethylene glycol sodium grafted nano-titanium dioxide; (4) According to the mass ratio of 100:35-80:1500-3000, sodium polyethylene glycol grafted nano titanium dioxide and a molecular formula of C 16 H 14 The 2-hydroxy-4-glycidyl ether-benzophenone of O4 is dispersed in a xylene solvent, stirred evenly, and reacted at 60-100°C for 6-15h. After the reaction is completed, it is filtered and washed with ethanol to obtain benzophenone-based polyethylene glycol-grafted nano-titanium dioxide; (5) Dissolve polylactic acid in a mixed solvent of dichloromethane and N,N-dimethylformamide in a mass ratio of 100:140-280:60-120:1.5-5, add benzophenone-based polyethylene glycol grafted nano-titanium dioxide after complete dissolution and stir evenly, then transfer it to a syringe, adjust the spinning distance to 15-25 cm, the spinning voltage to 15-20 kV, the spinning speed to 0.8-2 mL / h, and then perform electrospinning to obtain a UV-resistant polylactic acid composite fiber membrane.
[0018] Example 1
[0019] (1) Ultrasonic dispersion of 5 g of nano-titanium dioxide in 90 mL of toluene solvent was performed, and then 2 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added thereto. After stirring evenly, the temperature was raised to 70 °C for reaction for 2 h. After the reaction was completed, the nano-titanium dioxide was filtered and washed with ethanol to obtain epoxidized nano-titanium dioxide. (2) Dissolve 7.2 g of single-terminated amino polyethylene glycol in 96 mL of deionized water, adjust the pH to 9 with ammonia water, then add 4 g of epoxidized nano-titanium dioxide, and react at 60 ° C for 3 h. After the reaction is completed, filter and wash with deionized water to obtain polyethylene glycol-grafted nano-titanium dioxide; (3) 4 g of polyethylene glycol-grafted nano-titanium dioxide and 76 mL of toluene were placed in a reaction bottle, and the water was removed. Then, 0.012 g of metallic sodium was added under a nitrogen atmosphere, and the mixture was heated to 90 ° C for 12 h. After the reaction was completed, the mixture was filtered and washed with ethanol to obtain polyethylene glycol sodium-grafted nano-titanium dioxide; (4) 2g of sodium polyethylene glycol grafted nano-titanium dioxide and 0.7g of C 16 H 14 The 2-hydroxy-4-glycidyl ether-benzophenone of O4 was dispersed in 35 mL of xylene solvent, stirred evenly, and reacted at 60°C for 6 hours. After the reaction was completed, it was filtered and washed with ethanol to obtain benzophenone-based polyethylene glycol-grafted nano-titanium dioxide; (5) Dissolve 5 g of polylactic acid in a mixed solvent of 5.5 mL of dichloromethane and 4 mL of N,N-dimethylformamide. After complete dissolution, add 0.075 g of benzophenone-based polyethylene glycol-grafted nano-titanium dioxide and stir evenly. Transfer it to a syringe, adjust the spinning distance to 15 cm, the spinning voltage to 15 kV, and the spinning speed to 0.8 mL / h, and then perform electrospinning to obtain an anti-UV aging polylactic acid composite fiber membrane.
[0020] Example 2
[0021] (1) Ultrasonic dispersion of 5 g of nano-titanium dioxide in 100 mL of toluene solvent was performed, and then 2.5 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added thereto. After stirring evenly, the mixture was heated to 80 °C and reacted for 3 h. After the reaction was completed, the mixture was filtered and washed with ethanol to obtain epoxidized nano-titanium dioxide. (2) Dissolve 8 g of single-terminated amino polyethylene glycol in 100 mL of deionized water, adjust the pH to 9 with ammonia water, then add 4 g of epoxidized nano-titanium dioxide, and react at 70 ° C for 4 h. After the reaction is completed, filter and wash with deionized water to obtain polyethylene glycol-grafted nano-titanium dioxide; (3) 4 g of polyethylene glycol-grafted nano-titanium dioxide and 90 mL of toluene were placed in a reaction bottle, the water was removed, and then 0.02 g of metallic sodium was added under a nitrogen atmosphere, heated to 100 ° C for 18 h, and after the reaction was completed, filtered and washed with ethanol to obtain polyethylene glycol sodium-grafted nano-titanium dioxide; (4) 2g of sodium polyethylene glycol grafted nano-titanium dioxide and 1g of the molecular formula C 16 H 14The 2-hydroxy-4-glycidyl ether-benzophenone of O4 was dispersed in 45 mL of xylene solvent, stirred evenly, and reacted at 70°C for 8 hours. After the reaction was completed, it was filtered and washed with ethanol to obtain benzophenone-based polyethylene glycol-grafted nano-titanium dioxide; (5) Dissolve 5 g of polylactic acid in a mixed solvent of 6 mL of dichloromethane and 5 mL of N,N-dimethylformamide. After complete dissolution, add 0.1 g of benzophenone-based polyethylene glycol-grafted nano-titanium dioxide and stir evenly. Transfer it to a syringe, adjust the spinning distance to 18 cm, the spinning voltage to 16 kV, and the spinning speed to 1 mL / h, and then perform electrospinning to obtain an anti-UV aging polylactic acid composite fiber membrane.
[0022] Example 3
[0023] (1) Ultrasonic dispersion of 5 g of nano-titanium dioxide in 160 mL of toluene solvent was performed, and then 3 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added thereto. After stirring evenly, the temperature was raised to 90 °C for reaction for 5 h. After the reaction was completed, the nano-titanium dioxide was filtered and washed with ethanol to obtain epoxidized nano-titanium dioxide. (2) Dissolve 10 g of single-terminated amino polyethylene glycol in 140 mL of deionized water, adjust the pH to 10 with ammonia water, then add 4 g of epoxidized nano-titanium dioxide, and react at 80 ° C for 7 h. After the reaction is completed, filter and wash with deionized water to obtain polyethylene glycol-grafted nano-titanium dioxide; (3) 4 g of polyethylene glycol-grafted nano-titanium dioxide and 125 mL of toluene were placed in a reaction bottle, the water was removed, and then 0.03 g of metallic sodium was added under a nitrogen atmosphere, heated to 110 ° C for reaction for 32 h. After the reaction was completed, the mixture was filtered and washed with ethanol to obtain polyethylene glycol sodium-grafted nano-titanium dioxide; (4) 2g of sodium polyethylene glycol grafted nano-titanium dioxide and 1.4g of C 16 H 14 The 2-hydroxy-4-glycidyl ether-benzophenone of O4 was dispersed in 55 mL of xylene solvent, stirred evenly, and reacted at 90°C for 12 hours. After the reaction was completed, it was filtered and washed with ethanol to obtain benzophenone-based polyethylene glycol-grafted nano-titanium dioxide; (5) Dissolve 5 g of polylactic acid in a mixed solvent of 8 mL of dichloromethane and 7 mL of N,N-dimethylformamide. After complete dissolution, add 0.2 g of benzophenone-based polyethylene glycol-grafted nano-titanium dioxide and stir evenly. Transfer it to a syringe, adjust the spinning distance to 22 cm, the spinning voltage to 18 kV, and the spinning speed to 1.6 mL / h, and then perform electrospinning to obtain an anti-UV aging polylactic acid composite fiber membrane.
[0024] Example 4
[0025] (1) Ultrasonic dispersion of 5 g of nano-titanium dioxide in 170 mL of toluene solvent was performed, and then 4 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added thereto. After stirring evenly, the mixture was heated to 100 °C and reacted for 6 h. After the reaction was completed, the mixture was filtered and washed with ethanol to obtain epoxidized nano-titanium dioxide. (2) Dissolve 12 g of single-terminated amino polyethylene glycol in 160 mL of deionized water, adjust the pH to 10 with ammonia water, then add 4 g of epoxidized nano-titanium dioxide, and react at 90 ° C for 8 h. After the reaction is completed, filter and wash with deionized water to obtain polyethylene glycol-grafted nano-titanium dioxide; (3) 4 g of polyethylene glycol-grafted nano-titanium dioxide and 135 mL of toluene were placed in a reaction bottle, and the water was removed. Then, 0.04 g of metallic sodium was added under a nitrogen atmosphere, and the mixture was heated to 120° C. and reacted for 36 h. After the reaction was completed, the mixture was filtered and washed with ethanol to obtain polyethylene glycol sodium-grafted nano-titanium dioxide; (4) 2g of sodium polyethylene glycol grafted nano-titanium dioxide and 1.6g of C 16 H 14 The 2-hydroxy-4-glycidyl ether-benzophenone of O4 was dispersed in 65 mL of xylene solvent, stirred evenly, and reacted at 100°C for 15 hours. After the reaction was completed, it was filtered and washed with ethanol to obtain benzophenone-based polyethylene glycol-grafted nano-titanium dioxide; (5) Dissolve 5 g of polylactic acid in a mixed solvent of 10 mL of dichloromethane and 8 mL of N,N-dimethylformamide. After complete dissolution, add 0.25 g of benzophenone-based polyethylene glycol-grafted nano-titanium dioxide and stir evenly. Transfer it to a syringe, adjust the spinning distance to 25 cm, the spinning voltage to 20 kV, and the spinning speed to 2 mL / h, and then perform electrospinning to obtain an anti-UV aging polylactic acid composite fiber membrane.
[0026] Comparative Example 1 (1) Ultrasonic dispersion of 5 g of nano-titanium dioxide in 100 mL of toluene solvent was performed, and then 3 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added thereto. After stirring evenly, the mixture was heated to 80 °C and reacted for 4 h. After the reaction was completed, the mixture was filtered and washed with ethanol to obtain epoxidized nano-titanium dioxide. (2) Dissolve 9 g of single-terminated amino polyethylene glycol in 120 mL of deionized water, adjust the pH to 10 with ammonia water, then add 4 g of epoxidized nano-titanium dioxide, and react at 80 ° C for 5 h. After the reaction is completed, filter and wash with deionized water to obtain polyethylene glycol-grafted nano-titanium dioxide; (3) Dissolve 5 g of polylactic acid in a mixed solvent of 6 mL of dichloromethane and 5 mL of N,N-dimethylformamide. After complete dissolution, add 0.1 g of polyethylene glycol-grafted nano-titanium dioxide and stir evenly. Transfer it to a syringe, adjust the spinning distance to 15 cm, the spinning voltage to 18 kV, and the spinning speed to 1 mL / h, and then perform electrospinning to obtain an anti-UV aging polylactic acid composite fiber membrane.
[0027] Comparative Example 2 (1) Ultrasonic dispersion of 5 g of nano-titanium dioxide in 120 mL of toluene solvent was performed, and then 3 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added thereto. After stirring evenly, the temperature was raised to 90 °C for reaction for 2 h. After the reaction was completed, the nano-titanium dioxide was filtered and washed with ethanol to obtain epoxidized nano-titanium dioxide. (2) Dissolve 5 g of polylactic acid in a mixed solvent of 6 mL of dichloromethane and 5 mL of N,N-dimethylformamide. After complete dissolution, add 0.1 g of epoxidized nano-titanium dioxide and stir evenly. Transfer it to a syringe, adjust the spinning distance to 25 cm, the spinning voltage to 20 kV, and the spinning speed to 1.2 mL / h, and then perform electrospinning to obtain a UV-resistant polylactic acid composite fiber membrane.
[0028] Under light-free conditions, the mechanical properties of the polylactic acid composite fiber membrane resistant to UV aging were tested in accordance with the national standard GB / T 29284-2012.
[0029]
[0030] After 2 days of illumination, the mechanical properties of the polylactic acid composite fiber membrane resistant to UV aging were tested in accordance with the national standard GB / T 29284-2012.
[0031]
Claims
1. A polylactic acid composite fiber membrane resistant to ultraviolet aging, characterized in that: The method for preparing the anti-ultraviolet aging polylactic acid composite fiber membrane comprises the following steps: (1) Ultrasonic dispersion of nano-titanium dioxide in toluene solvent, then adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane, stirring evenly, heating to 70-100°C for reaction for 2-6 hours, filtering after the reaction, washing with ethanol to obtain epoxidized nano-titanium dioxide; (2) dissolving the single-terminated amino polyethylene glycol in a deionized water solution, adjusting the pH to 9-10 with ammonia water, and then adding epoxidized nano-titanium dioxide to react. After the reaction is completed, filtering, and washing with deionized water to obtain polyethylene glycol-grafted nano-titanium dioxide; (3) placing polyethylene glycol grafted nano-titanium dioxide and toluene in a reaction bottle, removing moisture, then adding metallic sodium under a nitrogen atmosphere, heating to the reaction temperature for reaction, filtering after the reaction is completed, and washing with ethanol to obtain polyethylene glycol sodium grafted nano-titanium dioxide; (4) Grafting sodium polyethylene glycol onto nano-titanium dioxide and 16 H 14 The 2-hydroxy-4-glycidyl ether-benzophenone of O4 is dispersed in a xylene solvent, stirred evenly, and reacted. After the reaction is completed, the mixture is filtered and washed with ethanol to obtain benzophenone-based polyethylene glycol-grafted nano-titanium dioxide; (5) Dissolve polylactic acid in a mixed solvent of dichloromethane and N,N-dimethylformamide. After complete dissolution, add benzophenone-based polyethylene glycol grafted nano-titanium dioxide and stir evenly. Transfer it to a syringe, adjust the spinning distance to 15-25 cm, the spinning voltage to 15-20 kV, and the spinning speed to 0.8-2 mL / h, and then perform electrospinning to obtain an anti-UV aging polylactic acid composite fiber membrane.
2. The anti-ultraviolet aging polylactic acid composite fiber membrane according to claim 1, characterized in that: In the step (1), the mass ratio of nano-titanium dioxide, toluene and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 100:1500-3000:40-80.
3. The anti-ultraviolet aging polylactic acid composite fiber membrane according to claim 1, characterized in that: In the step (2), the mass ratio of the single-terminated amino polyethylene glycol, deionized water and epoxidized nano-titanium dioxide is 180-300:2400-4000:
100.
4. The anti-ultraviolet aging polylactic acid composite fiber membrane according to claim 1, characterized in that: In the step (2), the reaction temperature is 60-90° C. and the reaction time is 3-8 h.
5. The anti-ultraviolet aging polylactic acid composite fiber membrane according to claim 1, characterized in that: In the step (3), the mass ratio of polyethylene glycol grafted nano-titanium dioxide, toluene and metallic sodium is 100:1600-3000:0.3-1.
6. The anti-ultraviolet aging polylactic acid composite fiber membrane according to claim 1, characterized in that: In the step (3), the reaction temperature is 90-120° C. and the reaction time is 12-36 hours.
7. The anti-ultraviolet aging polylactic acid composite fiber membrane according to claim 1, characterized in that: In the step (4), the mass ratio of the polyethylene glycol sodium grafted nano-titanium dioxide, 2-hydroxy-4-glycidyl ether-benzophenone and xylene is 100:35-80:1500-3000.
8. The anti-ultraviolet aging polylactic acid composite fiber membrane according to claim 1, characterized in that: In the step (4), the reaction temperature is 60-100° C. and the reaction time is 6-15 h.
9. The anti-ultraviolet aging polylactic acid composite fiber membrane according to claim 1, characterized in that: In the step (5), the mass ratio of polylactic acid, dichloromethane, N,N-dimethylformamide and benzophenone-based polyethylene glycol grafted nano-titanium dioxide is 100:140-280:60-120:1.5-5.
Citation Information
Patent Citations
Preparation method of anti-ultraviolet polylactic acid fiber
CN109338503A
A UV-resistant polylactic acid composite material and its preparation method
CN109401250B
Cited By
Antibacterial fiber and preparation process
CN121700542A
Antibacterial fiber and manufacturing process
CN121700542B